Dynamics of Emergency Cardiovascular Hospital Admissions and In-Hospital Mortality During the COVID-19 Pandemic: Time Series Analysis and Impact of Socioeconomic Factors - Álvarez-Martín, Claudia; Ribera, Aida; Marsal, Josep Ramon; Ariza-Solé, Albert; Pérez-Hoyos, Santiago; Oristrell, Gerard; Soriano-Colomé, Toni; Romaguera, Rafael; Pijoan, Jose Ignacio; Lidón, Rosa M.; Mauri, Josepa; Ferreira-González, Ignacio (Frontiers in Cardiovascular Medicine, 2022)
Aims: To evaluate the decline and in-hospital mortality or urgent cardiovascular hospital admissions during the COVID-19 pandemic in two successive waves. To evaluate differences by sex, age and deprivation index subgroups. Methods and results: Acute cardiovascular hospital episodes during years 2019-2020 were obtained from regional-wide data on public healthcare usage for the population of Catalonia (nord-east Spain) We fitted time-models to estimate the incidence rate ratios (IRR) of acute coronary syndrome (ACS) and acute heart failure (HF) admissions during the first pandemic wave, the between-waves period, and the second wave compared with the corresponding preCOVID19 periods, and to test for the interaction with sex, age and area based socioeconomic level. We evaluated the effect of COVID19 period on in-hospital mortality. ACS (n=8636) or HF (n=27,566) episodes were defined using primary diagnostic ICD-10 codes. ACS and HF admissions decreased during the first wave (IRR=0.66, 95%CI: 0.58-0.76 and IRR=0.61, 95% CI:0.55-0.68), during the second wave (IRR=0.80, 95%CI:0.72-0.88 and IRR=0.76, 95%CI: 0.69-0.84); acute HF admissions also decreased in the period between waves (IRR: 0.81, 95%CI: 0.74-0.89). The impact was similar in all sex and socioeconomic subgroups, and higher in older patients with ACS. In-hospital mortality was higher than expected only during the first wave. Conclusions: During the first wave of the COVID-19 pandemic there was a marked decline in urgent cardiovascular hospital admissions that was attenuated during the second wave. Both the decline and the attenuation of the effect have been similar in all subgroups regardless of age, sex or socioeconomic status. In-hospital mortality for ACS and HF episodes increased during the first wave, but not during the second.